2017
DOI: 10.3390/cryst7090271
|View full text |Cite
|
Sign up to set email alerts
|

Spark Plasma Sintering of Tungsten Oxides WOx (2.50 ≤ x ≤ 3): Phase Analysis and Thermoelectric Properties

Abstract: Abstract:The solid-state reaction of WO 3 with W was studied in order to clarify the phase formation in the binary system W-O around the composition WO x (2.50 ≤ x ≤ 3) during spark plasma sintering (SPS). A new phase "WO 2.82 " is observed in the range 2.72 ≤ x ≤ 2.90 which might have the composition W 12 O 34 . The influence of the composition on the thermoelectric properties was investigated for 2.72 ≤ x ≤ 3. The Seebeck coefficient, electrical conductivity and electronic thermal conductivity are continuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…We plotted the reported κ of c-WO x (white square) for comparison. Although c-WO x shows an inverse linear dependency of the observed κ obsd on x , i.e., 1.3 W m –1 K –1 ( x = 2.98) to 12 W m –1 K –1 ( x = 2.72), a-WO x films did not show such tendency; κ obsd is in the range from ∼0.9 W m –1 K –1 ( x = 2.982) to ∼1.6 W m –1 K –1 ( x = 2.642), which is far lower than that of c-WO x (Figure a). Note that the porous structure of the a-WO x films ( x > 2.93) deposited at higher P O 2 (>2.5 Pa) would show a slightly lower κ obsd .…”
Section: Resultsmentioning
confidence: 84%
“…We plotted the reported κ of c-WO x (white square) for comparison. Although c-WO x shows an inverse linear dependency of the observed κ obsd on x , i.e., 1.3 W m –1 K –1 ( x = 2.98) to 12 W m –1 K –1 ( x = 2.72), a-WO x films did not show such tendency; κ obsd is in the range from ∼0.9 W m –1 K –1 ( x = 2.982) to ∼1.6 W m –1 K –1 ( x = 2.642), which is far lower than that of c-WO x (Figure a). Note that the porous structure of the a-WO x films ( x > 2.93) deposited at higher P O 2 (>2.5 Pa) would show a slightly lower κ obsd .…”
Section: Resultsmentioning
confidence: 84%
“…It suggested that single phase W18O49 can be straightforwardly synthesized by reaction of WO3 and WO2 during the reactive SPS. This is remarkable, since other reports regarding the synthesis of monolithic ceramic W18O49 would involve multiple complicated steps 9,28,29) . In order to elucidate the anisotropic orientations, XRD patterns are shown in expanded 2θ sections, from 22° to 27° (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Tungsten oxide is also n-type, and there is little work dealing with its thermoelectric performance. Non-stoichiometric tungsten oxide, prepared by SPS, showed moderate thermoelectrical properties, with a maximum zT = 0.061 for WO 2.90 at 963 K. [140] Something similar is happening with vanadium, where low values for relevant thermoelectric applications have also been reported for vanadium oxide, without relevant results for this material so far. [141] Finally, non-stoichiometric cobalt oxides are among the metal oxides with the highest zT values have been reported.…”
Section: Earth-abundant Oxidesmentioning
confidence: 97%
“…Vapor deposition techniques such as atomic layer deposition, [152] sputtering, [127] molecular beam epitaxy, [153] or pulsed laser deposition [133,154] can also be used to form highly crystalline oxides. Finally, sintering methods such as SPS [140] or solid-state reactions [138] have also been used to form certain metal oxides…”
Section: Earth-abundant Oxidesmentioning
confidence: 99%